2018
DOI: 10.1097/md.0000000000010831
|View full text |Cite
|
Sign up to set email alerts
|

Poor prognostic role of the pretreatment platelet counts in colorectal cancer

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 35 publications
3
27
0
Order By: Relevance
“…In the 1960s, Richard B observed that the platelet count is elevated in patients with cancers compared to those with nonmalignant diseases [5]. Accumulating evidence suggests that elevated platelet counts are associated with various cancers, such as colorectal cancer, lung cancer, and endometrial carcinoma [12,65,66]. Platelets sustain proliferative signalling, resist cell death, and induce tumour angiogenesis [67].…”
Section: Discussionmentioning
confidence: 99%
“…In the 1960s, Richard B observed that the platelet count is elevated in patients with cancers compared to those with nonmalignant diseases [5]. Accumulating evidence suggests that elevated platelet counts are associated with various cancers, such as colorectal cancer, lung cancer, and endometrial carcinoma [12,65,66]. Platelets sustain proliferative signalling, resist cell death, and induce tumour angiogenesis [67].…”
Section: Discussionmentioning
confidence: 99%
“…In the 1960s, Richard B observed that the platelet count is elevated in patients with cancers compared to those with nonmalignant diseases 5 . Accumulating evidence suggests that elevated platelet counts are associated with various cancers, such as colorectal cancer, lung cancer, and endometrial carcinoma 12,66,67 . Platelets sustain proliferative signalling, resist cell death, and induce tumour angiogenesis 68 .…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1960s, RICHARD B had observed that platelet count elevated in patients with cancers compared to those with nonmalignant diseases 5 . Accumulating evidence suggesting that elevated platelet is associated with various cancers such as colorectal cancer, lung cancer, endometrial carcinoma and so on 12,66,67 .…”
Section: Discussionmentioning
confidence: 99%